Synthesis and characterization of π-conjugated copolymers with thieno-imidazole units in the main chain: application for bulk heterojunction polymer solar cells1. Issue 12 (28th March 2015) - Keshtov, M. L.; Godovsky, D. Yu.; Chen, F. C.; Khokhlov, A. R.; Siddiqui, S. A.; Sharma, G. D.
<x xml:space="preserve">Abstract</x> Three D–A conjugated copolymers P1, P2 and P3 based on different weak donors and the same acceptor unit, were used as donors for BHJ solar cells and achieved a PCE of 6.76%.